Evidence‐based teaching: Tools and techniques that promote learning in the psychology classroom. (5th February 2013) - Dunn, Dana S.; Saville, Bryan K.; Baker, Suzanne C.; Marek, Pam
Abstract Evidence‐based teaching (EBT) entails the use of empirically validated pedagogical tools and techniques that promote student learning. We offer a rationale for why psychology instructors should embrace EBT in their classrooms. We then review five areas of evidence offering specific tools and techniques that improve learning and retention: the testing effect, spaced learning, metacognition, writing to learn, and interteaching. We then briefly discuss how three student self‐regulated choices can promote learning. Finally, we urge psychology teachers and students to use the discipline's experimental findings to enhance student learning.